Acicular ferrite and bainite in C–Mn and low-alloy steel arc weld metals. (17th November 2018) - Abson, D. J.
ABSTRACT: Acicular ferrite is recognised as a desirable microstructural constituent in C–Mn and low-alloy steel weld metals. It is Widmanstätten ferrite that nucleates on the spheroidal non-metallic inclusions and grows by a reconstructive (diffusion-controlled) mechanism that proceeds substantially to completion. With increasing alloy content and/or cooling rate, the transformation to acicular ferrite may not be completed before the formation of bainite begins, the efficacy of inclusions in modern weld metal being such that colonies of bainite can nucleate on inclusions, forming by a displacive (shear) transformation mechanism, and producing colonies of similar size to acicular ferrite laths. Hence, in arc welds deposited with modern welding consumables, both acicular ferrite and intragranular bainite may form. As a consequence of the similarity in appearance of these two microstructural constituents in the optical microscope, some confusion in terminology has been introduced into the literature. This review seeks to eradicate this confusion.